2023
DOI: 10.1111/sms.14526
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different midsole foam in advanced footwear technology use on running economy and biomechanics in trained runners

Víctor Rodrigo‐Carranza,
Wouter Hoogkamer,
José María González‐Ravé
et al.

Abstract: BackgroundEthylene and vinyl acetate (EVA) and polyether block amide (PEBA) are recently the most widely used materials for advanced footwear technology (AFT) that has been shown to improve running economy (RE). This study investigated the effects of these midsole materials on RE and biomechanics, in both fresh and worn state (after 450 km).MethodsTwenty‐two male trained runners participated in this study. Subjects ran four 4‐min trials at 13 km‧h−1 with both fresh EVA and PEBA AFT and with the same models wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Worobets et al (2014) observed a 1% running economy improvement from EVA to TPU (thermoplastic polyurethane) midsole foam. Rodrigo- Carranza et al (2024) studied separate AFT shoe models, both with similar, but not identical, carbon fiber plate, tall stack height and rocker geometry, and with different midsole foams and found a 1.8% better running economy in the shoes with (fresh) PEBA foam than in the shoes with (fresh) EVA foam. Similarly, we observed a 1.0% improvement in running economy on average between EVA and PEBA foam, while using identical shoe models, controlling all other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Worobets et al (2014) observed a 1% running economy improvement from EVA to TPU (thermoplastic polyurethane) midsole foam. Rodrigo- Carranza et al (2024) studied separate AFT shoe models, both with similar, but not identical, carbon fiber plate, tall stack height and rocker geometry, and with different midsole foams and found a 1.8% better running economy in the shoes with (fresh) PEBA foam than in the shoes with (fresh) EVA foam. Similarly, we observed a 1.0% improvement in running economy on average between EVA and PEBA foam, while using identical shoe models, controlling all other variables.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature indicating that the new more resilient and compliant midsole foams are of greater importance than increased LBS in improving RE when using AFT [20, 35, 36]. Recently, we showed on separate occasions that AFT shoes with a curved carbon fiber plate and a highly resilient and compliant midsole improved RE by 1%–2% over shoes with a curved carbon fiber plate and traditional midsole [37, 38]. It may be that the ~2.5% improvement from the Stiff versus Control condition in the current study resulted from a ~ 1% improvement from increased LBS (similar to those reported in previous studies [14, 15]) and the remainder of the improvement from using more compliant and resilient midsole materials in combination with the curved carbon fiber plate.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature indicating that the new more resilient and compliant midsole foams are of greater importance than increased LBS in improving RE when using AFT (Healey & Hoogkamer, 2022;Kram, 2022). Recently, we showed on separate occasions that AFT shoes with a curved carbon fiber plate and a highly resilient and compliant midsole (PEBA) improved RE by 1-2% over shoes with curved carbon fiber plate and traditional midsole (EVA) (Lino et al, 2023;Rodrigo-Carranza, Hoogkamer, González-Ravé, Horta-Muñoz, et al, 2023). It may be that the ~2.5% improvement from the Stiff versus Control condition in the current study resulted from a ~1% improvement from increased LBS (similar to reported in previous studies (Oh & Park, 2017;Roy & Stefanyshyn, 2006)) and the remainder of the improvement from using more compliant and resilient midsole materials in combination with the curved carbon fiber plate.…”
Section: Discussionmentioning
confidence: 99%